The Representation of Women’s Status in Domestic and Political Patriarchy in Mary Astell and Mary Wollstonecraft - Guyonne Leduc (Revue Française de Civilisation Britannique)
Mary Astell (1666-1731) and Mary Wollstonecraft (1759-1797) dealt with the representation of women’s status in domestic and political patriarchy as constructive, and proposing thinkers. They denounced women’s status and submission, and criticised many aspects of patriarchy, seeing women as reasoning creatures and claiming that they should be treated as men are.After a presentation of the writers and their works highlighting their common points and differences, the analysis of both writers’ representations of women’s status in domestic and political patriarchy examines particular aspects in law and social practices such as education and marriage. We finally focus on the constructive side of Astell and Wollstonecraft’s criticism and on their purpose: to educate women not to please men but as rational creatures and to give enlightened women a better and more equal place.